2020
DOI: 10.1001/jamanetworkopen.2020.21463
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Mild Traumatic Brain Injury and Recovery in a Concussion Clinic Population

Abstract: IMPORTANCEPediatric mild traumatic brain injury (TBI) and concussion are a public health challenge with up to 30% of patients experiencing prolonged recovery. Pediatric patients presenting to concussion clinics often have ongoing impairments and may be at increased risk for persistent symptoms. Understanding this population is critical for improved prognostic estimates and optimal treatment. OBJECTIVE To describe pediatric patients presenting to concussion clinics and characterize factors associated with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…PTH 3 months and 6 months following injury was more common in those with PTH-M than PTH-NM, but this difference was only significant in the univariable analysis at 3 months ( Table 2 ). Given the strong association between female sex and prolonged recovery in prior studies, 1 , 2 , 17 recovery time and PTH at 3 months was analyzed in each PTH group to compare the sexes. Within each PTH phenotype, there was no significant difference in recovery or rates of PTH at 3 months between the sexes (eTable 5 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…PTH 3 months and 6 months following injury was more common in those with PTH-M than PTH-NM, but this difference was only significant in the univariable analysis at 3 months ( Table 2 ). Given the strong association between female sex and prolonged recovery in prior studies, 1 , 2 , 17 recovery time and PTH at 3 months was analyzed in each PTH group to compare the sexes. Within each PTH phenotype, there was no significant difference in recovery or rates of PTH at 3 months between the sexes (eTable 5 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…27 Similarly, pediatric patients, aged 12 to 18 years, with preexisting emotional distress (eg, depression and anxiety) exhibited longer symptom resolution relative to patients without a history of depression or anxiety. 39 Importantly, the authors also reported that girls and women experienced longer recovery times as well as higher percentages of preexisting anxiety compared with men. However, this study included patients presenting to a specialty concussion clinic at a median of 16 days after injury.…”
Section: Discussionmentioning
confidence: 92%
“…According to their comprehensive research, individuals suffering from moderate-to-severe TBI carry an elevated risk of disordered behavior and cognition. These impairments hinder patients' physical and occupational rehabilitation and social reintegration, resulting in an overall poorer quality of life (QoL) [15]. The findings from Schoenhuber and Gentilini also highlighted the relationship between mild head trauma and the risk of later developing certain psychiatric ailments [12].…”
Section: Discussionmentioning
confidence: 99%